Are paediatric stabbings in London related to socioeconomic status?. (October 2019) - Lam, Christine; Aylwin, Christopher; Khan, Mansoor
Introduction: Paediatric stabbings are on the increase across the United Kingdom, especially in large urban centres. Many London trauma centres are reporting a significant annual rise in the cases of penetrating trauma. Studies have shown victims with a lower socioeconomic status have an increased risk of paediatric penetrating trauma. This study aims to determine whether high depravity of an area increases the risk of paediatric stabbings in West London. We hypothesise that more deprived areas are likely to have a higher incidence of paediatric stabbings. Methods: A retrospective review of data from the emergency department at a major trauma centre in West London was conducted using patient <18 years with a stabbing injury between March 2015 and July 2017. Gender, age, incident postcode and home postcode were collected. Socioeconomic status was measured using the 2015 English index of multiple deprivation. Incident postcode and home postcode were matched to an index of multiple deprivation decile, with 1 being the most deprived. Data were analysed using SPSS© Statistics 24. Results: One hundred seventy-four cases were included; 97.7% of the cases were male and the mean age was 16 years. The location of the stabbings had a median index of multiple deprivation score of 3 (interquartile range = 3) with 61% of the cases occurring in areas with an index of multiple deprivation decile of 3 or less. Index of multiple deprivation decile from incident location and frequency of stabbing were strongly negatively associated (r = −0.85, p = 0.002). The victim's home location had a median index of multiple deprivation score of 3 (interquartile range = 3) and 59.3% of victims living in areas with an index of multiple deprivation decile of less than 3. Again, they were strongly negatively associated (r = −0.85, p = 0.002). Conclusion: The location of paediatric stabbings is associated with areas of high depravity and with victims from a more deprived background. To prevent paediatric stabbings, a multifactorial approach is required to increase the socioeconomic status of these areas.